Synthesis, reactivity and catalytic application of ferrocenyl-functionalized 1,2,3-triazol-5-ylidene complexes - Bezuidenhout, Daniela I. (2026)
Dissertation (MSc (Chemistry))--University of Pretoria, 2016.